Update on Gender-Affirming Treatment for the Transgender Woman - Unger, Cecile A. (Seminars in Reproductive Medicine, 2017)
Transgender women often transition with cross-sex hormone therapy and some opt to further affirm themselves with breast augmentation, facial feminization procedures, and/or vaginoplasty surgery. When considering medical and surgical transition for the transgender woman, careful preoperative evaluation and individual assessment is imperative and the World Professional Association for Transgender Health (WPATH) Standards of Care provide the framework from which health care providers and surgeons may assess eligibility for affirming treatments. Vaginoplasty for the transgender woman may be performed by a variety of techniques, mainly penile inversion vaginoplasty or intestinal segment vaginoplasty. Surgical outcomes vary according to technique, and the unique risks, advantages, and disadvantages must be considered. Outcomes appear to be satisfactory following vaginoplasty surgery, but prospective, long-term data are still lacking. Providers should be aware of the peri- and postoperative management of the transgender women after genital surgery, as many women require ongoing care and management after surgery.
Keywords: male-to-female vaginoplasty; transgender woman; transgender surgery; gender affirmation surgery